2022
DOI: 10.1093/jee/toac126
|View full text |Cite
|
Sign up to set email alerts
|

Bumble Bee Breeding on Artificial Pollen Substitutes

Abstract: Bumble bees are important pollinators for many temperate crops. Because of the growing demand for food from entomophilous crops, bumble bee colonies are commercially reared and placed in fields or greenhouses to guarantee sufficient pollination services. Besides, commercial colonies are increasingly used in laboratories for various bioassays under controlled conditions. For both usages, bumble bee colonies are commonly provided with sugar solution and honey bee-collected pollen pellets. However, the latter dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Thus, production of colonies in North America alone requires over 21,000 kg of honey bee-collected pollen annually. So far, artificial diets have not provided sufficient protein for bumble bee colony development and require supplementation with pollen (Bortolotti et al 2020, Gekière et al 2022). Restricting pollen to bumble bee colonies can lead to negative impacts on colony health and growth, creating a great need for honey bee-collected pollen in production (Rothman et al 2019, Rowe et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, production of colonies in North America alone requires over 21,000 kg of honey bee-collected pollen annually. So far, artificial diets have not provided sufficient protein for bumble bee colony development and require supplementation with pollen (Bortolotti et al 2020, Gekière et al 2022). Restricting pollen to bumble bee colonies can lead to negative impacts on colony health and growth, creating a great need for honey bee-collected pollen in production (Rothman et al 2019, Rowe et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be interpreted with caution, as it partly contrasts with the study of Palmer-Young et al [ 47 ] who showed that C. bombi cells developing in vitro resistance towards the phytochemical eugenol did not have a higher infectiousness than naïve parasite cells in eugenol-fed bumble bees. Regarding fat body content, although it is commonly used as a proxy for individual immunocompetence e.g., [ 31 , 34 , 38 , 48 ], underlying mechanisms remain poorly understood, making difficult clear interpretations of any effect. In prophylactic treatments, poppy pollen led to slightly higher fat body content than sunflower and multifloral pollen, whereas heather pollen led to reduced fat body content when compared to any other diet in therapeutic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…One way to overcome this limitation would be to rely on a diet shift rather than on a starvation–feeding transition, by providing bumble bee microcolonies with a specialized metabolite-free and nutritionally well-balanced diet prior to feeding them with pollen candidates [ 39 ]. However, hitherto, researchers have failed to develop a specialized metabolite-free artificial diet which supports bumble bee colony growth [ 48 , 68 ]. Moreover, even such an artificial diet could lead to experimental limitation as central metabolites (i.e., carbohydrates, proteins and lipids) play pivotal roles in host–parasite interactions (e.g., see [ 69 ] for the importance of sugars for in vitro Crithidia bombi growth).…”
Section: Discussionmentioning
confidence: 99%
“…Queenless microcolonies of five workers were exposed to specific diet treatments (Fig. 1): control pollen (i.e., willow pollen is used because of unsuitability of artificial pollen for bumblebee development; Gekière et al, 2022b) containing either (i) parasitised or (ii) non-parasitised bumble bees; heather pollen containing either (iii) parasitised or (iv) non-parasitised bumble bees; microcolonies fed with willow pollen supplemented with extracts of flavonoids from heather pollen containing either (v) parasitised or (vi) non-parasitised bumble bees. Diets (i) and (ii) were used as controls as well as to assess the parasite impacts.…”
Section: Bumble Bee Bioassaysmentioning
confidence: 99%